Economic Evaluation of Exercise-Based Cardiac Rehabilitation Programs for Chronic Heart Failure Patients in Colombia. Issue 1 (January 2016) - Rincón, Mónica; Rojas, Maria Ximena; Rodriguez Romero, Viviana Alejandra; Tamayo, Diana Carolina; Franco, Camilo; Castro, Hector; Brophy, James; Dennis, Rodolfo
Abstract : PURPOSE: Cardiac rehabilitation (CR) in patients with chronic heart failure (CHF) has met with resistance from third-party payers in low- and middle-income countries because of lack of evidence regarding its cost-effectiveness. We aimed to provide information to help better inform this decision-making process. METHODS: Costs associated with a 12-week exercise-based rehabilitation program in Colombia for patients with CHF were estimated. We collected data on all medical resources used in ambulatory care and data on hospital costs incurred for treating patients with uncompensated CHF. A literature search to establish the hospitalization rates because of uncompensated CHF, death because of CHF, and potential decreases in these data because of the utilization of CR was conducted. We modeled incremental costs and effectiveness over a period of 5 years from the perspective of the third-party payer. RESULTS: All costs were converted from Colombian pesos to US dollars. For an exercise-based CR program of 12-week duration (36 sessions), costs ranged from US265 to US369 per patient. Monthly costs associated with ambulatory care of CHF averaged US128 ± US321 per patient, and hospitalization costs were US3621 ± US5 444 per event. Yearly hospitalization incidence rates with and without CR were 0.154 and 0.216, respectively. The incremental cost of CR would be US998 per additional quality-adjusted life-year. Sensitivity analysis did not significantly change these results. CONCLUSIONS: Cardiac rehabilitation in patients with CHF in settings such as Colombia can be a cost-effective strategy, with minimal incremental costs and better quality of life, mainly because of decreased rates of hospitalization. Abstract : We estimated the cost-effectiveness of cardiac rehabilitation in patients with chronic heart failure in Colombia, a low- to middle-income country. Effectiveness was determined from the literature; direct medical costs for treating chronic heart failure and costs of cardiac rehabilitation were locally estimated. Cardiac rehabilitation is a cost-effective strategy, mainly because of decreased rates of hospitalization.